Financial risk management system (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article describes the The activity of economic entities is taking place in the scope of risks, in particular, it is observed that financial risk occupies a special place among them. In the current conditions, the financial risk arising in the process of formation